Genveje i den elektroniske bilingvale ordbog illustreret ved hjælp af man -> you, one, we, they og syntaktiske løsninger - Lenstrup, Rita (Nordiske Studier i Leksikografi, 2006)
Short cuts in an electronic bilingual dictionary illustrated by man ÷ you, one, we, they and syntactic solutions. Generally speaking, advanced language students in Denmark fail to tackle the non-existence of a full equivalent of the Danish indefinite pronoun man competently when expressing themselves in English – they heavily overuse the partial equivalent you. German and French have similar pronouns: man and on, but their dictionaries, just like Danish-produced English grammars, make a better point of warning and of offering solutions than do most Danish- English active dictionaries. On the basis of the combined material from dictionaries and grammars, this paper provides a suggestion for a flow chart for the Danish lemma man, intended for an electronic, dynamic, active Danish-English dictionary with links to external sources such as corpora and word lists.